Scoring System Otomatis Pada Lomba Menembak Dengan Target Sillhouette Hewan Menggunakan Logika Fuzzy - Handoko Ramadhan; Rizal Maulana; Mochammad Hannats Hanafi Ichsan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The shooting competition is one of the sport to practice concentration. In a shooting race with an animal-shaped sillhouette target, the use of the Automatic Countdown Tool (PSO) is still rarely used. In this study will make automatic score counters in the shooting race with animal sillhouette targets using fuzzy logic in determining the type of sillhouette target and the value of scores issued on the system. Fuzzy logic is used in the sillhouette type classification process to influence the score on the competition. This prototype is built using several modules that are Load Cell, Vibration Sensor, Limit Switch, Module HX711, and use Arduino UNO and Arduino Mega 2560 as its processor. Based on the results of shooting with an animal-shaped sillhouette, compared to the manual performed by officers, the scoring system provides good results. The accuracy of this system is 94.97% on the accuracy of sensor data. The system can also classify the type of sillhouette using fuzzy logic with an accuracy rate of 100%.